Language curriculum development to increase students’ interest in communication and literacy in higher education: a qualitative study - Razali Razali; Lina Sundana; Ramli Ramli; Teuku Alamsyah; Wahdaniah Wahdaniah (Cogent Education)
This study investigates language curriculum development in higher education, focussing on increasing students’ interest in communication and literacy. It discusses the curriculum’s implementation, factors influencing literacy interest, the role of communication practice-based learning, and its effectiveness in preparing students for the workforce. Using a qualitative approach with a case study design in several universities in Aceh, data were collected through in-depth interviews, curriculum analysis, and classroom observations. The findings reveal that the current curriculum does not effectively enhance students’ communication skills, especially globally. The main barriers include low material relevance and limited technology integration in learning. Practice-based learning methods have proven more effective in engaging students than traditional approaches. The study concludes that the curriculum needs to be updated to better align with global workforce demands, emphasizing adaptability to social, cultural, and technological changes.